Adsorption of Ce3+ ions using a one-dimensional nanomaterial with natural halloysite-kaolinite dual components - Phuong, Thao Le Thi; Kim, Thoa Nguyen Thi; Thi, Duyen Le (International Journal of Advanced Engineering Research and Science, 2023)
Rare earth elements are widely used in many technological domains, including reactants, alloying elements, catalysts, batteries, superconductors, etc., because of their unique electro-optical properties. Recovery and separation of rare earth elements are particularly crucial due to the steadily rising demand, as they can enhance scarce resources and reduce radiation-related waste disposal harm. Reports about the harmful effects of rare earth elements on microbes, plants, and animals have become increasingly common in recent years. More dangerously, residues from rare earth elements can build up in the human body through ingestion or digestion in the food chain. Finding a practical and affordable way to use rare earth elements or remove them from our surroundings is therefore essential. To extract these elements, halloysite is processed using a straightforward chemical procedure to produce rare earth metal ion adsorbent materials. The Halloysite that has been processed has a rod-shaped, one-dimensional nanomorphology. Halloysite-kaolinite is the two-phase version of the adsorbent material. The strong adsorption capacity of halloysite for Ce3+ is demonstrated by research findings. Halloysite adsorbs Ce3+ using the monolayer physical adsorption model and the pseudo-second-order adsorption kinetic equation.